Modern monologues for young people: a collection of humorous roya lty-free dramatic sketches for teen-agers - Murray, John, 1923- (Boston : Plays, Inc., 1961)
Twenty-five short monologues dramatizing in lighthearted fashion the ups and downs of life as seen by today's young people.
Keywords: Monologue